Linguistic Types of Code-Switching as a Medium of Solidarity in Eat, Pray, Love Movie - Juanita Eka Saputri; Fajar, Muh.; Heny Sulistyowati (Universitas PGRI Adi Buana Surabaya, 2024)
Accommodation theorists argue that speakers use different varieties of language to express solidarity with or social distance from their interlocutors (Howard Giles et al, 1991; Mukenge &Chimbarange, 2012). The studies of code-switching nowadays use various medias such as novels, movies, or short videos. In this research, the researchers uses movie to analysed the code-switching used. The purposes of this research are to find out the linguistic types of code-switching used by the characters in Eat, Pray, Love Movie and to explain about how the characters’ use of code-switching to express solidarity. The method used in this research is descriptive qualitative because the data taken by the researchers is in the form of dialogue in Eat, Pray, Love Movie. The source of the data is Eat, Pray, Love Movie by Ryan Murphy released in 2010. Data collection was done by downloading the Eat, Pray, love Movie transcription, watching and coding the data using Nvivo. Data analysis is done by analysed the data in Domain Table, Taxonomy Table, and Componential Table. The findings of this research shows that there are 30 data of code-switching which divided into 9 of Inter-Sentential Switching, 11 of Intra-Sentential Switching, and 10 of Tag Switching. Then, from the total 30 data of code-switching there are 14 data which express solidarity. These data are divided into 2 of Switching in Situational Change, 3 of Switching as a Signal of Group Membership or Shared Ethnicity, and 9 of Switching because of Participants Identity or Relationship.